Application to Determine Toddler Nutritional Status Using a Web-Based Fuzzy Mamdani Method - Khoirunnisya; Nurhasanah; Kevin Novebrianto (Jurnal Inotera, 2025)
The nutritional status of toddlers is vital for assessing their health and growth, but it involves many interrelated variables, making it complex to determine. The Fuzzy Mamdani method, developed by Prof. H.J. Zimmermann in the 1970s, uses fuzzy logic to handle concepts like "a little," "enough," or "a lot," which are more intuitive than binary values. This method can be effectively implemented in a web-based application to accurately determine toddlers' nutritional status. Such an application supports medical personnel by providing efficient and accurate assessments, facilitating appropriate care and interventions.